2009
DOI: 10.1182/blood-2009-03-212449
|View full text |Cite
|
Sign up to set email alerts
|

Hairy cell leukemias with unmutated IGHV genes define the minor subset refractory to single-agent cladribine and with more aggressive behavior

Abstract: Hairy cell leukemia (HCL) is generally

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 43 publications
5
93
0
1
Order By: Relevance
“…Although the percentage of IGHV4-34 genes that were unmutated was similar for HCLc and HCLv (83% vs 100%, P ϭ .4), the reported percentage of unmutated IGHV4-34 rearrangements in CLL (21% of 159 rearrangements) 6 was much lower than in the present study of HCLc (P ϭ .007) or HCLv (P Ͻ .001). IGHV1-69, observed in HCLc ( Figure 3B; n ϭ 5) but not in HCLv, was always mutated, in contrast to CLL, where 241 (87%) of 277 rearrangements were unmutated (P Ͻ .001) 5,6 Of several independent studies of gene usage in HCL rearrangements from a total of 191 specimens obtained before treatment, 10,[14][15][17][18]23 only one rearrangement expressing IGHV1-69 was reported, and it was also mutated. 23 None of the 5 HCLc IGHV1-69 sequences was from allele *01, compared with 214 (83%) of 259 CLL rearrangements that were from allele *01 (P Ͻ .001), 177 (83%) of which had 100% homology to germline.…”
Section: Igh Mutation Statusmentioning
confidence: 92%
See 1 more Smart Citation
“…Although the percentage of IGHV4-34 genes that were unmutated was similar for HCLc and HCLv (83% vs 100%, P ϭ .4), the reported percentage of unmutated IGHV4-34 rearrangements in CLL (21% of 159 rearrangements) 6 was much lower than in the present study of HCLc (P ϭ .007) or HCLv (P Ͻ .001). IGHV1-69, observed in HCLc ( Figure 3B; n ϭ 5) but not in HCLv, was always mutated, in contrast to CLL, where 241 (87%) of 277 rearrangements were unmutated (P Ͻ .001) 5,6 Of several independent studies of gene usage in HCL rearrangements from a total of 191 specimens obtained before treatment, 10,[14][15][17][18]23 only one rearrangement expressing IGHV1-69 was reported, and it was also mutated. 23 None of the 5 HCLc IGHV1-69 sequences was from allele *01, compared with 214 (83%) of 259 CLL rearrangements that were from allele *01 (P Ͻ .001), 177 (83%) of which had 100% homology to germline.…”
Section: Igh Mutation Statusmentioning
confidence: 92%
“…IGHV1-69, observed in HCLc ( Figure 3B; n ϭ 5) but not in HCLv, was always mutated, in contrast to CLL, where 241 (87%) of 277 rearrangements were unmutated (P Ͻ .001) 5,6 Of several independent studies of gene usage in HCL rearrangements from a total of 191 specimens obtained before treatment, 10,[14][15][17][18]23 only one rearrangement expressing IGHV1-69 was reported, and it was also mutated. 23 None of the 5 HCLc IGHV1-69 sequences was from allele *01, compared with 214 (83%) of 259 CLL rearrangements that were from allele *01 (P Ͻ .001), 177 (83%) of which had 100% homology to germline. 6 The IGHV3-23 gene, the most common gene found in HCLc, was unmutated only in one case, very different from IGHV4-34 (P Ͻ .001).…”
Section: Igh Mutation Statusmentioning
confidence: 92%
“…Splenomegaly (> 3 cm), leukocytosis (>10 × 10 9 /L), hairy cells in the blood (> 5 × 10 9 /L), and high beta2‐microglobulin (> 2N) are associated with a poor prognosis and resistance to purine analogs (PNA) 8. In a similar manner to chronic lymphocytic leukemia (CLL), CD38 expression drives poor prognosis 9.…”
Section: How the Diagnosis Of Hcl And Hcl‐like Disorders Has Improvedmentioning
confidence: 99%
“…High resolution genomic profiling in HCL, comparing it to HCL-variant, has demonstrated in both diseases a number of chromosome gains and losses, namely in chromosomes 5 and 7q [15]. However and in contrast to HCL-variant, losses at 17p --a region that codes for the tumor suppressor gene TP53 or mutations of this gene --were not found in HCL and have rarely been reported in this disease [16]. The high frequency of TP53 abnormalities in HCL-variant may well underline its refractoriness to agents that are very effective in HCL.…”
Section: Laboratory Featuresmentioning
confidence: 99%
“…Patients with bulky abdominal lymphadenopathy tend to have suboptimal responses to purine analog therapy [10]. One study has suggested that the uncommon HCL cases with IgHV4-34 usage or with unmutated IgVH are those that more often do not respond to the purine analog CDA [16,32]. The very minority of HCL that have TP53 abnormalities may also have an unfavorable outcome.…”
Section: Prognostic Factors and Outcomementioning
confidence: 99%